Development of Mobile Application for Applying Aquaponic Techniques in Farming Using Augmented Reality Approach - Lai, Yi Chien; Ismail, Mohd Norasri (Applied Information Technology And Computer Science, 2022)
Aquaponics is integrated agriculture that combines aquaculture and hydroponics techniques where the culture water is recirculating which reduced the production of wastewater and produced 100% organic food sources. Based on the research, the mobile application that provides augmented reality (AR) in the agriculture area, especially aquaponics is still lacking. Also, most available related mobile application needs to be purchased while others lack multimedia elements. Hence, the main objective of the project is to design the aquaponics mobile application using an augmented reality approach. Besides, the other objectives are developing the application using the Android platform and performing functional testing and user acceptance testing on the target user. Multimedia Mobile Content Development is used as the methodology of the project. The application provides 8 topics of information, a video guide on building the aquaponics system and a 3D model to help the target users in visualizing the model. The user acceptance test showed more than 80% of positive responses which indicated the users are satisfied with the application. Future work can be done by adding more 3D model designs and interactivity in the AR session.